Computation of the electric field at multipoint cathodes; Soviet Physics Journal; Vol.18, № 11 - Belomytsev S. Ya.; Bugaev S. P.; Litvinov E. A.; Mesyats G. A. Gennady Andreyevich; Ilyin A. P. Aleksandr Petrovich (1976, 1976)
В фонде НТБ ТПУ отсутствует